In vitro characterization of an enzymatic redox cascade composed of an alcohol dehydrogenase, an enoate reductases and a Baeyer–Villiger monooxygenase - Oberleitner, Nikolin (J Biotechnol, 2014)
An artificial enzyme cascade composed of an alcohol dehydrogenase, an enoate reductase and a Baeyer–Villiger monooxygenase was investigated in vitro to gain deeper mechanistic insights and understand the assets and drawbacks of this multi-step biocatalysis. Several substrates composed of different structural motifs were examined and provided access to functionalized chiral compounds in high yields (up to >99%) and optical purities (up to >99%). Hence, the applicability of the presented enzymatic cascade was exploited for the synthesis of biorenewable polyesters.